Six-core versus twelve-core prostate biopsy: a retrospective study comparing accuracy, oncological outcomes and safety. (February 2016) - Mohammed, W.; Davis, N.; Elamin, S.; Ahern, P.; Brady, C.; Sweeney, P.
Abstract Aims To compare sextant and 12 core transrectal ultrasound-guided (TRUS) prostate biopsies for detecting prostate cancer (PCa) and to determine whether 12-core prostate biopsies are associated with a higher incidence of insignificant prostate cancer and complications. Methods A retrospective study was performed on all patients with a positive TRUS biopsy for prostate cancer between January 2011 and December 2013. Group A underwent a sextant core prostate biopsy and group B underwent a 12-core prostate biopsy. Outcome variables were cancer detection rates, oncological outcomes, incidence of clinically insignificant PCa and incidence of biopsy associated complications. Exclusion criteria included a negative TRUS biopsy and metastatic prostate cancer. Result In total 718 prostate biopsies were performed and 286 patients met inclusion criteria (143 patients in each group). The overall cancer detection rate was 43 % in group A compared to 53 % in group B (p = 0.03). In group A, 31 (21.7 %) patients proceeded to open retropubic radical prostatectomy (RRP) compared to 36 (25.2 %) in group B (p = 0.7). Sextant biopsies were associated with a significantly higher rate of upgrading compared to 12-core biopsies in RRP specimens (51.6 versus 25 % respectively, p < 0.01). The incidence of clinically insignificant PCa was 10.5 % in group A versus 14.7 % in group B (p = 0.2). The incidence of urosepsis post biopsy was 0.7 % in both groups (n = 1). Conclusion Twelve-core biopsies were associated with higher PCa cancer detection rates, greater accuracy for Gleason grading and no differences for detecting clinically insignificant PCa or urosepsis compared to sextant biopsies.